The Role of Organizational Commitment as a Predictor of Organizational Citizenship Behavior in Employees: A Literature Review - Muhammad Fikrie Hisram Aziz; Rahmawati Prihastuty (Journal of Social and Industrial Psychology, 2025)
Organizational Citizenship Behavior (OCB) represents employees' voluntary work contributions that exceed formal job descriptions and are crucial for organizational effectiveness. However, its emergence is influenced by various factors. Organizational commitment, defined as employees' psychological bond with their organization, is believed to be a fundamental predictor of OCB. This research aims to comprehensively analyze the role of organizational commitment in fostering OCB among employees, addressing the research gap of existing inconsistent empirical findings. This study employs a Systematic Literature Review (SLR) approach guided by PRISMA. Data were collected from 20 national and international journal databases with a publication range of 2015-2025, using the keywords "organizational commitment" and "organizational citizenship behavior". From 127,499 initial findings, after a rigorous identification and screening process, 16 relevant articles were further analyzed. The synthesis results predominantly indicate that organizational commitment has a positive and significant influence on OCB across various industrial, sectoral, and geographical contexts. However, the analysis also reveals significant variations in this influence. Some studies found a non-significant relationship, and the magnitude of organizational commitment's influence on OCB varied. It can be concluded that organizational commitment is a valid antecedent for OCB, but the strength of its influence varies considerably.